The Effect of Pursed Lip Breathing and Diaphragmatic Breathing on Increasing Oxygen Saturation in COPD Patients - Tonika Tohri; Metilda; Sindi Sugandi (Journal Of Nursing Practice, 2025)
Background: Chronic Obstructive Pulmonary Disease (COPD) is a progressive respiratory condition marked by continuous airflow limitation, often resulting in hypoxemia and hypercapnia. The WHO (1) projects that by 2030, COPD will rank as the third leading cause of death globally. In Indonesia, the prevalence of COPD reached 2.4% in 2018. One of the key clinical manifestations of COPD is a decline in oxygen saturation. Non-pharmacological breathing techniques such as Pursed Lip Breathing (PLB) and Diaphragmatic Breathing (DB) have been shown to improve ventilation and oxygenation. Purpose: This study aimed to determine the effectiveness of PLB and DB in improving oxygen saturation among COPD patients. Methods: A quasi-experimental one-group pre-post test design was used, involving 30 purposively selected COPD patients from a population of 35 treated. Each participant performed PLB and DB for 5-10 minutes per session, three times daily, for four weeks-initially during hospitalization and later at home under supervision. Inclusion criteria were COPD patients with oxygen saturation levels of 88–90% who had not previously received PLB or DB therapy. Exclusion criteria included those with prior experience of PLB/DB, anxiety, anti-anxiety treatment, as anxiety can alter breathing patterns and reduce therapy effectiveness. Data were collected using observation sheets and pulse oximeters and analyzed with Wilcoxon Signed Rank Test. Results: Mean oxygen saturation increased from 89.40% (SD = 2.15) to 92.10% (SD = 1.98) with a significant p-value (0.000 < 0.05). Conclusion: PLB and DB effectively enhance oxygen saturation in COPD patients and have important implications for evidence-based nursing practice and education.